Satisfying medical and rehabilitation needs positively influences returning to work after a work-related injury: an analysis of national panel data from 2018 to 2019 - Suk Won Bae; Min-Yong Lee; Shin Who Park; Gangpyo Lee; Ja-Ho Leigh (BMC, 2021)
Abstract Background This study examined how meeting the medical needs of injured workers after initial treatment may affect their return to work, using data from the Panel Study of Workers' Compensation Insurance. Methods This study was designed as a longitudinal study, which used data from the second-year, follow-up survey conducted in the secondary cohort of the Panel Study of Workers' Compensation Insurance. The odds ratio (OR) and 95% confidence interval were estimated through binomial and multinomial logistic regression analyses to examine the effects of unmet medical needs on workers' return to original work and return to work overall (including reemployment). Results The returned to original work OR of workers whose rehabilitation needs were met was 1.35 (1.12-1.63) while the return to work OR was 1.20 (1.03-1.41). The returned to original work OR of workers whose medical needs were met was 1.64 (1.18-2.27) while the return to work OR was 1.39 (1.07-1.80). In terms of disability rating, the return to work ORs of workers with mild disabilities whose medical/rehabilitation needs were not met and those of workers without disabilities were 1.71 (1.17-2.49) and 1.97 (1.27-3.08), respectively. In the case of regular/temporary workers, the returned-to-work ORs of workers whose medical/rehabilitation needs were not met were 1.54 (1.12-2.13) and 1.27 (1.03-1.56), respectively. Conclusions For workers who sustained work-related injuries, providing medical accessibility and meeting rehabilitation needs were found to be important predictors of return to work after initial treatment.